The Effectiveness Of Monosodium Glutamate And Types Ofplanting Media On The Growth Of Orchid Plant (Dendrobium sp) In Acclimatization Phase - Suharman Suharman; Nurhapisah Nurhapisah (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2021)
The need for orchids in Indonesia are still very large, including the Dendrobium "Indonesia Raya" orchid which is still popular. Obstacles in orchid propagation are very slow growth at the acclimatization stage so that alternatives are needed to spur the vegetative growth of orchid plantlets whose materials are easily available and affordable. One of the efforts to spur growth is by using a combination of fern media, husk charcoal, and wood shavings and using Monosodium glutamate (MSG) as a fertilizer supplement in the growth of orchid plantlets at the aclimatization stage. This study aims to determine the effect of the type of planting medium and the application of monosodium glutamate (MSG) and its interaction on the growth of the Dendrobium "Indonesia Raya" orchid at the acclimatization stage. The method used was a 2-factor factorial randomized block design (RBD). The first factor was the type of planting medium, namely ferns, husk charcoal, wood shavings, ferns + husk charcoal, ferns + wood shavings, ferns + husk charcoal + wood shavings. The second factor is the dose of Monosodium glutamate, namely without MSG, 2.5 grams / liter of water and 5.0 grams / liter of water. Located in the Laboratory and Green House of the Department of Agriculture and Fisheries of Makassar City from December 2020 to February 2021. The results showed that the dose of Monosodium glutamate do not provide a significant response to the growth of orchid plantlets while the combination of fern + charcoal growing media could increase the vegetative growth of orchids. Dendrobium "Indonesia Raya" at the aclimatization stage.